THE ANALYSIS OF MODE CHOICE MODEL BASED ON TRIP-BASED AND TOUR-BASED IN A DAY - Agustien, Melawaty; Sjafruddin, Ade; Lubis, Harun Al Rasyid S.; Wibowo, Sony Sulaksono (Prosiding Forum Studi Transportasi Antar Perguruan Tinggi, 2015)
The weakness of mode choice model based on trip-based and tour-based is not paying attention to how the characteristics of the activity influence the alternative modes used to conduct such activities. Regarding this, the mode choice model in this study based on the activity schedule and the time allocation. The mode choice model for the three alternatives such as private car, private motorcycle and other modes in this study is developed with the multinomial logit choice model based on the utility time allocation model of activity choice in a day. The selection mode is used to conduct the activity choice at the time after returning home from working activities.The result of the empirical analysis shows that the attributes of individuals, families and activities greatly affect the utility of time allocation of activities such as sports, shopping, meetings, entertainment and socialisation. Alternative modes that have greater attributes of utility activity value, shorter travel time, lower travel costs and joint tour have greater chance to be selected.